Non- Farm Enterprises And Secondary Child Schooling In Indonesia - Hendrawan Budi Susilo; Dias Satria (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2022)
This study aims to examine the influence of ownership of non-farm enterprises by households on child participation in a secondary school in Indonesia; this area of research has received scant attention in recent times. This paper uses the Indonesia Family Life Survey (IFLS) data set that contains different levels of data, ranging from individual-level data to community-level data for the analysis. Using a binomial logistic regression model, this study finds that the ownership of non-farm enterprises generally increases the likelihood of children's participation in secondary education, especially senior high school. Further estimation using propensity score matching demonstrates that households with non-farm enterprises tend to have higher spending on school expenses than those that do not have non-farm enterprises.